(untitled) (Global Journal of Human-Social Science, 2023)
Manta is one of the main coastal cities in Ecuador with the greatest tourist potential of sun and beach which over the years is one of the most prevalent That is why the main objective of this work was to carry out a characterization of the main tourist beaches of that city from the geographical ecotourism and environmental point of view as a contribution to the knowledge of each of these spaces of tourist interest The methodology used was based on the analysis of documentary review as well as field observation and the use of an information record sheet They also re-recognized with the application of geographic information systems GIS tools which allowed to identify physical elements on the beaches and represent them cartographically As result it was found that the beaches of the urban area of Manta have some weaknesses that have a negative impact on tourism including pollution of its waters and its overall space It is concluded that the beaches of the city of Manta have weaknesses in terms of conditions for tourism